2013
DOI: 10.1186/1743-0003-10-82
|View full text |Cite
|
Sign up to set email alerts
|

The cost of space independence in P300-BCI spellers

Abstract: BackgroundThough non-invasive EEG-based Brain Computer Interfaces (BCI) have been researched extensively over the last two decades, most designs require control of spatial attention and/or gaze on the part of the user.MethodsIn healthy adults, we compared the offline performance of a space-independent P300-based BCI for spelling words using Rapid Serial Visual Presentation (RSVP), to the well-known space-dependent Matrix P300 speller.ResultsEEG classifiability with the RSVP speller was as good as with the Matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…In a similar study, Chennu et. al., through an offline study, have shown that the classification accuracy is comparable between RSVP and matrix based paradigms, but without a language model the typing speed is relatively low while utilizing the RSVP paradigm [13]. In this study, we also compare the typing performance during online typing of both RSVP and matrix paradigms, using the aforementioned language-model-assisted BCI.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a similar study, Chennu et. al., through an offline study, have shown that the classification accuracy is comparable between RSVP and matrix based paradigms, but without a language model the typing speed is relatively low while utilizing the RSVP paradigm [13]. In this study, we also compare the typing performance during online typing of both RSVP and matrix paradigms, using the aforementioned language-model-assisted BCI.…”
Section: Introductionmentioning
confidence: 96%
“…Many potential users from the target population, unfortunately, lack precise gaze control and for these users, it is anticipated that matrix paradigms will suffer from reduced performance. To overcome this dependency in BCI typing systems, different presentation schemes have been explored and shown to have comparable performances with the matrix presentation paradigm in terms of speed and accuracy [11], [12], [13]. Rapid serial visual presentation (RSVP) is one of these paradigms, in which symbols are presented sequentially in time, at a predefined fixed location on the screen and in a pseudorandom order [14], [5], [15], [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, relative to most matrix-based spellers, the RSVP Speller information transfer rate (ITR) is not satisfactory. Literature 44 , 45 indicates that the RSVP speller (which contains 28 characters) has only one-third of the ITR of the Matrix speller (which contains 36 characters). Therefore, improving the ITR of the RSVP speller system under the condition of ensuring RSVP speller recognition accuracy is an extremely meaningful subject of study.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,12] There are some disadvantages in matrix speller systems. [28][29][30][31] We proposed using RSVP, in which icons appear on the screen sequentially, at a predefined fixed location on the screen and in a pseudorandom order. Most importantly, lack of precise gaze control is very common in many potential users and results in reduced performance of the system.…”
Section: Resultsmentioning
confidence: 99%